Acceptance of Going Concern Audit Opinion with Audit Reputation as A Moderation Variable in Non-Cyclical Consumer Sector Companies Listed on The Indonesian Stock Exchange Period 2017-2022 - Sulia, Sulia; Loman, Devina; Situmorang, Iskandar Muda; Mie, Mie (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2024)
The objective of this research is to determine and analyze the influence of debt default, audit lag, previous year's audit opinion, and opinion shopping on the acceptance of going concern audit opinions. Apart from that, this research also aims to determine and analyze the ability of audit reputation to moderate the relationship between debt default, audit lag, previous year's audit opinion, and opinion shopping with the acceptance of going concern audit opinions in Non-Cyclical Consumer Sector Companies Listed on the Stock Exchange Indonesia for the 2017-2022 period. Sampling and data collection techniques have been determined, data adequacy and completeness have been determined and technical evaluation and prediction of results have been carried out. The research results show that the debt default and audit lag variables have no influence on the acceptance of going concern audit opinions. This is different from the previous year's audit opinion and opinion shopping which has a positive influence on the acceptance of going concern audit opinions. And for the moderating variable, audit reputation is unable to moderate the relationship of all independent variables to the dependent variable.